Caribbean Report 09-03-1992 - Crosskill, Hugh (anchor); Ninvalle, Pete (correspondent); Norton, Michael (correspondent); Reece, Donald (interviewee); Hobday, Peter (correspondent); Anyaoku, Emeka (interviewee); Perreira, Joseph 'Reds' (correspondent); Murray, Deryck (interviewee) (The British Broadcasting Corporation, 1992)
Speculation over the impending retirement of Jamaican Prime Minister Michael Manley should be confirmed after a meeting of the People's National Party (PNP) executive. A number of ministers are vying for the leadership position. St.Lucia’s Prime Minister John Compton is to announce the date for general elections on March 22nd taking advantage of the fall out the Opposition Leader Julian Hunte is experiencing since his violent attack on him. Haiti seeks parliamentary support for the OAS brokered accord in order to move forward with the ratification of Prime Minister Designate René Théodore before restoring President Aristide to office. Violence in Antigua continues with the firebombing of the home of Antiguan Speaker of the House, Casford Murray on Saturday. The Commonwealth Day address by Queen Elizabeth emphasises the implementation of environmental programs by member countries. Securing victory in the World Cup game is crucial to both the West Indian and Indian cricket teams if either one is to advance to the semi-final stage of the competition. Unconfirmed reports say that the West Indies will replace Malcolm Marshall with Phil Simmons in tonight’s game. Finally, Former West Indies Captain Viv Richards is set to launch his autobiography “Hitting Across the Line” in Australia today.
1. Headlines (00:00-00:31)
2. Widespread rumours of impending retirement of Jamaica’s Prime Minister Michael Manley are mounting (00:32-01:44)
3. St. Lucia’s Prime Minister to announce date for general elections on 22nd March. Correspondent Pete Ninvalle reports (01:45-03:53)
4. Legislators in Haiti need to ratify OAS brokered accord before democracy can be restored. Correspondent Michael Norton reports from Port-au-Prince (03:54-06:15)
Keywords: Patterson, P. J. (Percival James), 1935-; Political parties -- Jamaica -- Elections; Election forecasting -- Jamaica; People's National Party (Jamaica); Elections -- Saint Lucia; Compton, John, 1926-; United Workers Party (Saint Lucia); Treaties -- Ratification; Democratization -- Haiti; Haiti -- Politics and government; Incendiary bombs -- Antigua and Barbuda -- Antigua; Commonwealth countries -- Anniversaries, etc.; Cricket -- Tournaments -- West Indies; Cricket -- Tournaments -- India; Cricket players -- West Indies -- Biography; Hunte, Julian; Théodore, René; Reece, Donald; Murray, Casford; Commonwealth Day -- Anniversaries; World Cup (Cricket) (1992 : Australia; New Zealand); Viv Richards -- West Indian Cricketer -- Biography